CANCER CARERS MEDICINES MANAGEMENT: A FEASIBILITY TRIAL OF AN EDUCATIONAL INTERVENTION FOR MANAGING END OF LIFE PAIN MEDICATION. Issue 1 (1st March 2014) - Latter, S; Lowson, E; Hopkinson, J; Hughes, J; Richardson, A; Duke, S; Anstey, S; Bennett, M; May, C; Smith, P
Abstract : Introduction: A majority of people with advanced cancer will experience pain and family carers play an important role in managing pain medication at home. There is evidence carers need support with this, yet no research in the UK has developed and tested theory-driven interventions to help them manage pain medicines. We are conducting a Phase I-II feasibility study (MRC 2008) to develop a new intervention: Cancer Carer Medicines Management (CCMM). Aim(s) and method(s): To summarise Phase I, outlining the process of CCMM development. A staged multi-method approach was used to obtain current evidence to inform CCMM's development: a systematic literature review of interventions for carer end of life medicines management; a scoping of practice and theoretical contexts; interviews and user involvement group consultations with patients, carers, and health professionals with palliative care experience. This informed two participatory action research workshops to design and develop an intervention. The resulting prototype intervention was then further refined through a consultative review process. Results: This staged, collaborative approach is appropriate and successful in enabling an evidence-based, clinically applicable intervention to be developed. Conclusion(s): The intervention development process has ensured that CCMM reaches the feasibility trial stage with a robust grounding in carer experience, clinical practice and research evidence. In turn, the intervention has the potential to enhance the nurses' practice in the community to meet carers' needs in pain medication management.